Personality and affections in university students: implications of circadian typology - Santos, Giovanna de Almeida; Moreira, Juliana Oliveira; Araujo, Ana Maria Mazon; Teixeira, Gabriela Correia; Vaz, Nicolle Helena Carvalho; Fonseca, Júlia Gabriela Antunes; Andrade, Michael J. O (Sleep Science, 2022)
The chronotype refers to the individual differences related to the preference to perform activities or to rest during the wake or in the preferences for a certain period of the day. In this study, we evaluated how the chronotype can be considered a variable of interest for individual personality differences. Still, it was verified how the positive and negative effects and self-esteem interact with the quality of sleep and the circadian personality according to the Big Five personality factors. This study included 150 volunteers of both sexes (41 men and 109 women) aged between 16 and 44 years old (M=22.08; SD=3.8 in age). The analysis of variance showed significant differences for Horne and Ostberg [F(2.148) = 401.69; η2=0.85] usual sleep efficiency [F(2.148) = 4.83; η2=0.6] and the sleep quality index [F(2.148) = 3.25; η2=13.0]. Morning subjects had better behavioral indexes of sleep quality when compared to evening subjects. Regarding positive affects [F(2.147) = 3.54; η2=0.53], morning subjects had a higher score than afternoon subjects (p=0.34) and consequently had higher scores in kindness traits [F(2,148) = 6.81; η2=0.95] and emotional stability [F(2.188) = 6.58; η2=0.91]. The chronotype is associated with personality factors and sleep behavior (efficiency and sleep latency as basic requirements for good quality of sleep) and variables such as sleep efficiency and quality of sleep can be moderators of this behavior.
Keywords: Sleep; Personality; Students